2019
DOI: 10.1186/s12917-019-1870-4
|View full text |Cite
|
Sign up to set email alerts
|

Two novel amino acid substitutions in highly conserved regions of prion protein (PrP) and a high frequency of a scrapie protective variant in native Ethiopian goats

Abstract: Background Polymorphisms of the prion protein gene may influence scrapie susceptibility in small ruminants through modified protein conformation. At least 47 amino acid substitutions and 19 silent polymorphisms have been described in goat PRNP reported from several countries. The objective of this study was to investigate PRNP polymorphisms of native Ethiopian goat breeds and compare the results with other goat breeds. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…R154H variant in the Algerian breed has been reported in 15-26% of the study population 9 . The variant T193I was first reported in a recent study by Vitale M. et al, 2019 at a frequency similar to the current observation 12 . The overall frequency of serine to proline substitution at 240 positions in the present study was similar to Anatolian goat breeds (0.08) 26 but higher than the other Ethiopian goat as shown in the above table.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…R154H variant in the Algerian breed has been reported in 15-26% of the study population 9 . The variant T193I was first reported in a recent study by Vitale M. et al, 2019 at a frequency similar to the current observation 12 . The overall frequency of serine to proline substitution at 240 positions in the present study was similar to Anatolian goat breeds (0.08) 26 but higher than the other Ethiopian goat as shown in the above table.…”
Section: Discussionsupporting
confidence: 88%
“…NS146 was reported in 20.4% of healthy Cyproytic goats 27 . R154H variant was detected at a low frequency in Afar(present study), Western highland, Long Eared Somali, and Aegean region goat breeds 12,26 . R154H variant in the Algerian breed has been reported in 15-26% of the study population 9 .…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…Amino acids at codon 126 and 127 are localized in the highly conserved glycine rich motif GAVVG 126 G 127 LGGYMLG.This residue was reported to antagonize prion disease development by blocking amyloidal fibril formation [2]. A recent work by Vitale et al,2019 reported polymorphism at this position and implicated its importance in the normal cellular function of prion protein [21].The sequence variation in palindrome residue (PrP 113-120 ) and glycine repeat regions (PrP 124-128 ) synergistically may affect cellular prion protein conformational flexibility.…”
Section: Discussionmentioning
confidence: 99%